DEVELOPING ENGLISH LISTENING MATERIALS FOR THE TENTH GRADE STUDENTS OF TOURISM MAJOR IN VOCATIONAL SCHOOL - Simon Christofel Silalahi; Rahmad Husein; Anggraini Thesisia Saragih (Universitas Negeri Medan, 2017)
The objective of this study is to find out what the English listening materials are appropriate for students in tourism major. Indonesia has many spots for tourism then it makes government to improve the students’ ability in tourism major. Since the students need to communicate with other people especially tourist then it needs to improve listening skill. Because basically listening is a skill of English that consists of receiving, constructing, and responding to verbal or nonverbal massage. In fact, the finding of materials that provided for the Grade X students of Tourism major at SMK Negeri 7 Medan that listening materials provided in the textbook are not related to the students’ major. Then it is needed to develop the English listening materials for the tenth grade of tourism major. The research was conducted by using Research and Development (R&D) method. The subject of this research was 2016/2017 students of the tenth grade of tourism major in SMK Negeri 7 Medan. The number of the students was 26 students. The data of this study were collected by using need analysis questionnaire, and interview. It was found that 61.90% of the respondents assumed that existing listening materials are not related to their major, and 93.75% expected major-related English listening materials. The experts’ validation shows that the developed listening materials are appropriate and recommended to be used. At the end of this study, teachers are expected to be able to see the students’ needs and can prepare even develop the materials in order to meet students’ needs and job. Key words: Research and Development, English listening materials, Tourism